A RESTful web service to estimating time requirements for web forms. (1st January 2014) - Martin, Ludger
It is important to know whether a website or web application is usable. What you need are statistics about how the website is used. Such statistics usually include information about how much time a web user spends on a web page. But to know whether those dwell times are acceptable you will need reference values. This paper provides and discusses such reference values based on a research study. To allow automatic analysis of input elements a web service is presented to reveal any possible element. Using this service and the results of our study, any kind of HTML/HTML5 input elements in a web form can be analysed.